International Labour Regulation:: What Have We Really Learnt So Far? - Tsogas, George (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
Can soft regulatory approaches and corporate social responsibility ever be substitute methods for pursuing meaningfully across the globe violations of labour standards? Our analysis shows the limits of country, government, and hard-law based international labour regulation, but also the ambiguities and challenges of soft labour regulation. We introduce an updated model of international labour regulation and create a conceptual framework for analyzing labour regulation. We provide some insights into how regulation has developed over the last decades and discuss some of the challenges it faces. Our assessment of the various regulatory regimes is based on the simple premise of whether they can provide a venue for workers’ rights violations to be redressed. We aim to provide a broad overview and an attempt at generalizing the findings and “lessons learnt” so far from an international and comparative industrial relations perspective.